"Morram" os cariocas! o regionalismo paulista nas páginas esportivas (1901-1938) - Machado, Felipe Morelli (2016)
This work consists in an analysis of Sao Paulo regionalism in the sports pages in the early years of Brazilian soccer, from the study of the first inter-state matches that opposed Sao Paulo and Rio de Janeiro and the Brazilian participation in large-scale international soccer episodes, such as the South American Championship 1919 (played in Rio de Janeiro), the C. A. Paulistano tour to Europe (in 1925), and the first World Cups, occasions that mobilized national sporting life. The appreciation of these facts contribute to a broader reflection about the own move of São Paulo's elites against the neighbors of the capital of the Republic in a dispute over the cultural vanguard position of the nation, passing it can be even better apprehended from look that relationship of the sports press of Sao Paulo with soccer